2018
DOI: 10.1002/hed.25350
|View full text |Cite
|
Sign up to set email alerts
|

PI3‐kinase pathway biomarkers in oral cancer and tumor immune cells

Abstract: Background This study investigated the hypothesis that phosphoinositide 3‐kinase (PI3‐kinase) pathway dysregulation in either head and neck cancer cells and/or tumor infiltrating immune cells would influence outcomes of patients with surgically treated oral tongue squamous cell carcinomas (SCC). Methods We constructed tissue microarrays containing 123 oral tongue SCC samples and performed immunohistochemistry using antibodies against 7 PI3‐kinase pathway markers: phosphatase and tensin homolog (PTEN), Akt, p‐A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Patients with metastatic melanoma who initially responded to anti-PD-1 alone or in combination with anti-CTLA-4 and then progressed were analyzed, and PTEN-loss was identified in 5 cases in the post-progression biopsy out of 18 intact PTEN expression in pre-treatment biopsies ( 107 ). In surgically treated oral cavity squamous cell carcinomas, PTEN loss in tumor infiltrating immune cells has been associated with worse prognosis ( 108 ). Similarly to PTEN-loss, WNT-β-catenin promotes an immunosuppressive tumor microenvironment that may be responsible for secondary resistance to immunotherapy ( 106 , 109 ).…”
Section: Resistance To Immunotherapiesmentioning
confidence: 99%
“…Patients with metastatic melanoma who initially responded to anti-PD-1 alone or in combination with anti-CTLA-4 and then progressed were analyzed, and PTEN-loss was identified in 5 cases in the post-progression biopsy out of 18 intact PTEN expression in pre-treatment biopsies ( 107 ). In surgically treated oral cavity squamous cell carcinomas, PTEN loss in tumor infiltrating immune cells has been associated with worse prognosis ( 108 ). Similarly to PTEN-loss, WNT-β-catenin promotes an immunosuppressive tumor microenvironment that may be responsible for secondary resistance to immunotherapy ( 106 , 109 ).…”
Section: Resistance To Immunotherapiesmentioning
confidence: 99%
“…Increase in PI3K increases AKT, thereby suggesting a positive correlation between PI3K and ATK. Ibrahim M, et al found that activation of the PI3-kinase pathway in cancer cells was associated with higher risk of recurrence and/or death through activation of p-AKT pathway [13]. Multiple types of tumor malignancies have been identified to activate the PI3K/AKT pathway [14].…”
Section: Discussionmentioning
confidence: 99%
“…As a key protein in the Akt/PI3K signaling pathway, p-AKT (phosphorylated Akt) may be an important link between oxidative stress and cancer. Therefore, we researched a large number of studies and found that overexpression of p-AKT is firmly related to the prognosis of various hematologic tumors and solid tumors, such as non-small cell lung cancer (NSCLC) (5)(6)(7)(8), gastric cancer (GC) (9)(10)(11)(12), squamous cell carcinoma (SCC) (13)(14)(15)(16), hepatocellular carcinoma (HCC) (17)(18)(19), ovarian cancer (OC) (20,21), diffuse large B-cell lymphoma (DLBCL) (22,23), urothelial carcinoma (UC) (24,25), nasopharyngeal carcinoma (NC) (26), pediatric Burkitt lymphoma (PBL) (27), hairy cell leukemia (HCL) (28), peripheral T-cell lymphoma (PTCL) (29), anaplastic large cell lymphoma (ALCL) (30), breast cancer (BC) (31), endometrial carcinoma (EC) (32), and pancreatic cancer (PC) (33).…”
Section: Introductionmentioning
confidence: 99%